2019
DOI: 10.1097/j.pain.0000000000001770
|View full text |Cite
|
Sign up to set email alerts
|

Temporal instability of salience network activity in migraine with aura

Abstract: This study aims to investigate whether intra-network dynamic functional connectivity and causal interactions of the salience network is altered in the interictal term of migraine. 32 healthy controls, 37 migraineurs without aura and 20 migraineurs with aura were recruited. Participants underwent a T1-weighted scan and resting-state fMRI protocol inside a 1.5T MR scanner. We obtained average spatial maps of resting-state networks using group independent component analysis, which yielded subject-specific time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…With this pattern of thalamocortical connectivity in mind, we may hypothesize that the MRI pattern of normal thalamic microstructure and disrupted thalamocortical relationship detected in our MA patients could be due either to a pure cortical alteration, or to an alteration of thalamocortical fibre bundles. Previous studies in patients with exclusively visual aura showed widespread disruption of white matter fibre bundle architecture [ 8 , 9 , 11 ], which could contribute to the between-network disconnection found in our patients and in those from other research groups [ 12 , 16 ].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…With this pattern of thalamocortical connectivity in mind, we may hypothesize that the MRI pattern of normal thalamic microstructure and disrupted thalamocortical relationship detected in our MA patients could be due either to a pure cortical alteration, or to an alteration of thalamocortical fibre bundles. Previous studies in patients with exclusively visual aura showed widespread disruption of white matter fibre bundle architecture [ 8 , 9 , 11 ], which could contribute to the between-network disconnection found in our patients and in those from other research groups [ 12 , 16 ].…”
Section: Discussionsupporting
confidence: 59%
“…A major limitation of the two latter studies is lack of a control group, so that it is not clear to which extent presence and complexity of the aura have impacted imaging features of the normal brain [ 7 , 14 ]. In a recent resting state study using 1.5T fMRI, Veréb et al [ 16 ] detected a non-significant trend of weaker causal interaction from the DMN to the DAS in migraine with aura in comparison to HCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exponential weighted moving average method is applied to the standardized residuals to compute time-varying correlations (DCC). The strength and variability of dFC were quantified as the mean and standard deviation of the DCC over time [26,45]. The strength and variability of dFC were compared between groups using an unpaired two-sample t-test.…”
Section: Cross-correlation and Dynamic Functional Connectivity Analysismentioning
confidence: 99%
“…In contrast, dynamic functional connectivity (dFC), which considers temporal variations of functional connectivity, has provided novel insight into the understanding of dynamic properties of brain network for acute and chronic pain [16,24,25]. Recently, it has been reported that the variability of dFC within the salience network was higher in migraine with aura compared to healthy controls (HC) and migraineurs without aura [26]. Migraine patients exhibit abnormal thalamocortical dynamic functional network connectivity between the posterior thalamus and default mode and visual regions [27].…”
Section: Introductionmentioning
confidence: 99%